Cost-effectiveness of therapist-guided internet-delivered cognitive behaviour therapy for paediatric obsessive–compulsive disorder: results from a randomised controlled trial. Issue 5 (17th May 2017) - Lenhard, Fabian; Ssegonja, Richard; Andersson, Erik; Feldman, Inna; Rück, Christian; Mataix-Cols, David; Serlachius, Eva
Abstract : Objectives: To evaluate the cost-effectiveness of a therapist-guided internet-delivered cognitive behaviour therapy (ICBT) intervention for adolescents with obsessive–compulsive disorder (OCD) compared with untreated patients on a waitlist. Design: Single-blinded randomised controlled trial. Setting: A research clinic within the regular child and adolescent mental health service in Stockholm, Sweden. Participants: Sixty-seven adolescents (12–17 years) with a Diagnostic and Statistical Manual of Mental Disorders Fifth Edition diagnosis of OCD. Interventions: Either a 12-week, therapist-guided ICBT intervention or a wait list condition of equal duration. Primary outcome measures: Cost data were collected at baseline and after treatment, including healthcare use, supportive resources, prescription drugs, prescription-free drugs, school absence and productivity loss, as well as the cost of ICBT. Health outcomes were defined as treatment responder rate and quality-adjusted life years gain. Bootstrapped mixed model analyses were conducted comparing incremental costs and health outcomes between the groups from the societal and healthcare perspectives. Results: Compared with waitlist control, ICBT generated substantial societal cost savings averaging US−144.98 (95% CI −159.79 to –130.16) per patient. The cost reductions were mainly driven by reduced healthcare use in the ICBT group. From the societal perspective, the probability of ICBT being cost saving compared with waitlist control was approximately 60%. From the healthcare perspective, the cost per additional responder to ICBT compared with waitlist control was approximately US78. Conclusions: The results suggest that therapist-guided ICBT is a cost-effective treatment and results in societal cost savings, compared with patients who do not receive evidence-based treatment. Since, at present, most patients with OCD do not have access to evidence-based treatments, the results have important implications for the increasingly strained national and healthcare budgets. Future studies should compare the cost-effectiveness of ICBT with regular face-to-face CBT. Trial registration number: NCT02191631.